Neural correlates of apathy revealed by lesion mapping in participants with traumatic brain injuries. Issue 3 (13th February 2013) - Knutson, Kristine M.; Dal Monte, Olga; Raymont, Vanessa; Wassermann, Eric M.; Krueger, Frank; Grafman, Jordan
Abstract : Apathy, common in neurological disorders, is defined as disinterest and loss of motivation, with a reduction in self‐initiated activity. Research in diseased populations has shown that apathy is associated with variations in the volume of brain regions such as the anterior cingulate and the frontal lobes. The goal of this study was to determine the neural signatures of apathy in people with penetrating traumatic brain injuries (pTBIs), as to our knowledge, these have not been studied in this sample. We studied 176 male Vietnam War veterans with pTBIs using voxel‐based lesion‐symptom mapping (VLSM) and apathy scores from the UCLA Neuropsychiatric Inventory (NPI), a structured inventory of symptoms completed by a caregiver. Our results revealed that increased apathy symptoms were associated with brain damage in limbic and cortical areas of the left hemisphere including the anterior cingulate, inferior, middle, and superior frontal regions, insula, and supplementary motor area. Our results are consistent with the literature, and extend them to people with focal pTBI. Apathy is a significant symptom since it can reduce participation of the patient in family and other social interactions, and diminish affective decision‐making. Hum Brain Mapp 35:943–953, 2014. © 2013 Wiley Periodicals, Inc.